Social media livestreaming: Investor information or persuasion? - deHaan, Ed; Huang, Allen H.; Kannan, Srijith; Qiu, Lu (Journal of Accounting and Economics, 2026)
We analyze over 27,000 social media livestreams by Chinese mutual funds to investigate whether they achieve regulators’ goal of improving retail investment decisions. Our findings indicate that livestreams generate significant inflows, often within minutes of their start times. Yet rather than educating investors, livestreams amplify return-chasing behavior and predict sharp declines in fund performance. Investors who buy in response to livestreams would earn higher returns by holding index funds or even cash. Further analyses using deep learning algorithms reveal that livestreams are more persuasive when speakers are more physically attractive, use more positive language, and sound more excited. We conclude that livestreams primarily function as persuasive advertising and that regulators should be wary of educational efforts led by sellers of consumer financial products. We also conclude that prior evidence on the benefits of firms’ social media use in equity markets does not extend to financial product markets in this setting.